2015
DOI: 10.4102/rw.v6i1.77
|View full text |Cite
|
Sign up to set email alerts
|

Receptive vocabulary and early literacy skills in emergent bilingual Northern Sotho-English children

Abstract: This study explored receptive vocabulary size and early literacy skills (namely: letter naming, knowledge of phoneme-grapheme correspondences and early writing) in emergent bilingual Northern Sotho-English children. Two groups of Grade 1 learners were tested in both English and in Northern Sotho. Group 1 (N = 49) received their formal schooling in English, whilst group 2 (N = 50) received their formal schooling in Northern Sotho. Receptive vocabulary was tested using the Peabody Picture Vocabulary Test. Letter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…This may be because much of the effort in learning to read in the first year of schooling is focused on developing accurate decoding skills. However, locally, Wilsenach (2015) found receptive vocabulary to be a robust predictor of early literacy development in Northern Sotho-English emergent bilingual children. Although receptive vocabulary knowledge was found to be low in both Northern Sotho and English groups of learners, it had a significant effect on early literacy skills in both languages.…”
Section: Vocabulary and Readingmentioning
confidence: 91%
See 1 more Smart Citation
“…This may be because much of the effort in learning to read in the first year of schooling is focused on developing accurate decoding skills. However, locally, Wilsenach (2015) found receptive vocabulary to be a robust predictor of early literacy development in Northern Sotho-English emergent bilingual children. Although receptive vocabulary knowledge was found to be low in both Northern Sotho and English groups of learners, it had a significant effect on early literacy skills in both languages.…”
Section: Vocabulary and Readingmentioning
confidence: 91%
“…Vocabulary is also central to additional language learning, and adequate vocabularies are especially important for children for whom the FAL is also their LoLT. As prior local studies have suggested, young South African English FAL learners are struggling with vocabulary (Macdonald 1990;Sibanda 2014;Wilsenach 2015), but performance in the African HL is also a challenge (Pretorius & Mokhwesana 2009;Wilsenach 2015 The importance of vocabulary for reading achievement and for school success cannot be overstated. As this small-scale study shows, there is still much that we do not know about vocabulary development amongst South African learners.…”
Section: Concluding Thoughts and The Way Forwardmentioning
confidence: 99%
“…In South Africa, where many school-aged learners display below average language and literacy skills (Department of Basic Education, 2014 ; Howie, et al ., 2008 ; Wilsenach, 2015 ), the dilemma of failing learners probably remains the most serious and most common problem that teachers, educational psychologists, and SLTs encounter. In this context, the accurate assessment of processing problems, particularly those related to language and literacy achievement is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…( 2004 ) are of the opinion that reading difficulties in non-clinical groups are caused by environmental factors such as poverty, inadequate education, and social factors such as the age and education of a child’s mother and the child’s position in the family. Although all of these environmental factors probably contribute to the low literacy levels of South African learners, the causal role of underdeveloped phonological processing skills and vocabulary skills (see Wilsenach, 2015 ), which are strongly associated with non-word repetition, remains unclear in the South African context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In South Africa, Wilsenach ( 2015 ) found that receptive vocabulary size in emergent bilingual Northern Sotho–English children predicted the development of their early literacy skills. Children with a limited vocabulary not only lag behind their peers at school entry, but the gap widens as they progress through school.…”
Section: Introductionmentioning
confidence: 99%